Strategies for Time Domain Characterization of UWB Components and Systems - Pancera, Elena (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2009)
In this work new methods and criteria for the analysis of Ultra Wideband (UWB) components and systems are introduced. This permit to have a deeper insight into the component characteristics like signal distortion, ringing and dispersion, introduced by the non-ideal behavior of the UWB components over the wide frequency band. The developed analyses are the basis for correction and optimization strategies for the features of the UWB components and systems, compensating for their non-idealities.